ANALISIS PENGGUNAAN METODE ACTIVITY BASED COSTING (ABC) DALAM MENENTUKAN SUMBANGAN PEMBINAAN PENDIDIKAN (SPP) PADA POLITEKNIK HARAPAN BERSAMA - Ida Farida; Sunandar Sunandar; Hetika Hetika (Media Riset Akuntansi, Auditing & Informasi, 2017)
The purpose of this study to determine the calculation of education and tuition fee by using Activity Based Costing at the Polytechnic Harapan Bersama and compare the education and tuition fee by using Activity Based Costing before and after. Politeknik Harapan Bersama not have a special method to determine the cost of education. At the Polytechnic Joint expectations are two sources of income, namely Login or registration fees and donations Education Support (SPP) to be paid each month. To determine the calculation of Education and tuition fee by using Activity Based Costing at the Polytechnic of Harapan Bersama. To determine the ratio of Education and tuition fee by using Activity Based Costing before and after. Data analysis method used is descriptive method. Descriptive analysis of the data is the processing of research data in order to make this data meaningful (meaningful). SPP of tariff calculation using Activity Based Costing known SPP tariff rate is Rp. 370 189; From the results of the SPP tariff calculation using the method of Activity Based Costing, when compared with the SPP tariff band is used by schools today are using the traditional method, for example Rp. 350,000; so that the difference in the amount Ro. 20 189 ;. Rate differences that occur due to charging of overhead on each product. Activity Based Costing has been able allocate cost to each activity.